Ekspresi Burung Merpati Pada Kriya Kulit - Hidayah, Yosi; Sumadi, Sumadi; Hendratno, Hendratno (SPACEPRO: Product Design Jurnal, 2024)
The final project thesis entitled "Expression of Doves in Leather Craft" is inspired by human life in general which is visualized through doves. The life of living beings in this work is a sequence of stories that begins with a pair of pigeons, then lays eggs and hatches into chicks, and finally, these chicks have their respective partners. The main objects in these works are doves in various expressions. The background is adjusted to the object's atmosphere to interpret the story; the supporting objects are trees, birdhouses, mountains, waterfalls, and seeds as bird food. The creation of this thesis uses the theories of form, function, aesthetics, and expression through several stages of the process. The exploration stage is in the form of observation and finding references to pigeons as the idea of the work. The design stage is in the form of visual concepts with alternative sketches and selected designs. The realization stage on vegetable-tanned leather media using the pyrography technique. This technique uses an electric soldering tool. Meanwhile, the frame of the work uses your wood and the finishing of the work uses shoe polish, black paint, and clear doff for finishing the frame of the work. The works in this thesis amount to seven works of display with a size of 60 x 80 cm in the form of portraits, the titles of the works consist of honeymoon, warmth, livelihood, harmony, flying high, searching, and romance. Works with organized and ideal life stories in life as a hope for real life.